Interstitial Ectopic Pregnancy Report of Four Cases - Kars, Bülent; Alkan, Nevriye; Karşıdağ, Yasemin; Esim Büyükbayrak, Esra; Ünal, Orhan; Turan, Cem (Gynecology Obstetrics & Reproductive Medicine, 2009)
The aim of the present case series is to describe clinical presentation and ultrasonographic appearances observed in this rare form of ectopic pregnancy. We present 4 cases of interstitial ectopic pregnancy which were treated surgically at our institute over one year period. Interstitial pregnancy is a rare form of ectopic pregnancy which carries a higher risk of morbidity and mortality due to catastrophic hemorrhage. Early diagnosis is mandatory for management of this potentially fatal condition and a high index of suspicion is essential for early diagnosis.